XVIII congrès mondial de l’UISPP – Union Internationale des Sciences Préhistoriques et protohistoriques, Paris, 4–9 Juin 2018. / The 18th UISPP (International Union of the Prehistoric and Protohistoric Sciences) World Congress, Paris, June 4–9 2018. / 18. - Milena Gošić Arama (University of Belgrade, 2018)
-